2021
DOI: 10.1002/jts.22665
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Controlled Trial of Transcendental Meditation as Treatment for Posttraumatic Stress Disorder in Veterans

Abstract: Preliminary studies have demonstrated the efficacy of Transcendental Meditation (TM) for treating posttraumatic stress disorder (PTSD). The present study extended previous research with a pilot trial of TM as a treatment for PTSD via a single-blinded, randomized controlled design. veterans with PTSD (N = 40) were assigned to a TM intervention or treatment-as-usual (TAU) control group. Participants in the TM group engaged in 16 sessions over 12 weeks, primarily in a 60-min group format. Change in PTSD symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Meditation versus control group . Twenty-five studies (reported in 23 articles, n = 1825) assessed self-reported anxiety: 12 studies (in 10 references) evaluated TM [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] and 13 OMBM [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Meditation versus control group . Twenty-five studies (reported in 23 articles, n = 1825) assessed self-reported anxiety: 12 studies (in 10 references) evaluated TM [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] and 13 OMBM [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meditation versus control group . Twenty-two studies (reported in 23 articles, n = 1616) with data on self-reported depression were included in the MA: 13 evaluated TM [ 13 , 14 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 56 , 57 , 58 , 59 ]; 8 OMBM [ 36 , 38 , 40 , 42 , 45 , 46 , 50 , 51 , 60 ]; and 1 [ 61 ] evaluated a combination of mantra-based meditation, Tibetan sounds, and attention focused on breathing. Thirteen studies included clinical samples, and nine included adults from the general population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations